Frailty is associated with sociodemographic and health factors and related to the care context of older caregivers: a Brazilian cross-sectional study - Macedo, Marcela Naiara Graciani Fumagale; Alves, Élen dos Santos; Jesus, Isabela Thaís Machado de; Inouye, Keika; Brito, Tábatta Renata Pereira de; Orlandi, Ariene Angelini dos Santos (São Paulo Medical Journal, 2023)
BACKGROUND: The task of caring can arise suddenly without guidance or support, resulting in psychological tension and health impairment, which can culminate in the development of frailty. OBJECTIVE: To analyze the relationship between frailty and sociodemographic and health aspects related to the care context of older caregivers. DESIGN AND SETTING: A cross-sectional study was conducted on 65 older caregivers registered in family health units in the interior of the state of São Paulo. METHODS: The participants were interviewed individually using the following instruments: a characterization questionnaire, Fried’s frailty phenotype, Zarit Burden’s Interview, Mini-Mental State Examination, Geriatric Depression Scale, Katz Index, and Lawton Scale. In addition, the following statistical tests were applied: Pearson’s chi-squared test, Fisher’s exact test, and Mann–Whitney test. A significance level of 5% was considered to be statistically significant. RESULTS: Women who took care of their spouses predominated without prior training or the help of other people. Most of the patients were pre-frail (72.3%). Frailty was significantly related to marital status (P = 0.016), depressive symptoms (P = 0.029), cognitive decline (P = 0.029), the degree of kinship (P = 0.015), and burden (P = 0.004). CONCLUSION: Older caregivers without a partner, with severe depressive symptoms and cognitive changes, who cared for their parents, and had higher levels of burden, presented a higher proportion of frailty.